Knowledge, attitude, and practice of Chinese parents with infants (aged 0–3 years) toward immunity, gut microbiota and biotics: a comprehensive study - Wang, Jiongnan; Liu, Nan; Chen, Yufan; You, Jialu; Yang, Yunqing; Jin, Yi; Sun, Guiju; Zhou, Jin (Frontiers in Immunology, 2024)
In the wake of the COVID-19 pandemic, there has been an increasing focus towards infant immunity. The development and maintenance of the immune system are significantly influenced from birth, and is shaped by early-life infant feeding behavior. Hence, the knowledge, attitude, and practice (KAP) of parents play a crucial role in shaping the immune system of infants. A total of 2369 parents across 19 cities in China were surveyed using a self-designed online questionnaire. The KAP questionnaire assessed three domains: immunity, gut microbiota, and biotics (prebiotics, probiotics, and synbiotics). The questionnaire also included questions on infant health. An overwhelming majority of parents (97.90%) placed high value on their children's immunity, and 40.40% of them reported an increased level of concern following the COVID-19 pandemic. Diarrhea (78.80%), colds (75.70%), nighttime crying (73.80%), regurgitation (71.70%) and food retention (66.50%) were the major health issues reported. Knowledge scores toward immunity and gut microbiota were positively correlated to attitude and practice scores, respectively. Attitude scores toward immunity, gut microbiota and biotics were positively correlated to their respective practice scores. Parental knowledge score on immunity was negatively correlated with diarrhea, colds, regurgitation and food retention. On the other hand, parental practice scores toward immunity were negatively correlated with food retention. In regards to gut microbiota, parental knowledge score was negatively correlated with diarrhea, regurgitation and food retention; parental attitude score was negatively correlated with nighttime crying whereas practice score was negatively correlated with diarrhea, regurgitation, food retention and nighttime crying. Attitude score toward biotics was negatively correlated with nighttime crying and practice scores toward biotics was negatively correlated with colds, food retention and nighttime crying. This study demonstrated that significant gaps and misunderstandings exist among parents regarding immunity, gut microbiota health, and biotics. Both public education and interventions are crucial to enhance parental knowledge and practices, thereby improving infant immunity.